Using the logistic model to study the most important factors that distinguish between the infected And not infected with malignancies - مدرس مساعد / زينب عبداهلل محمد (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
In this Research analysis of the discrimination of Logistics model is used, which discriminately between patients infected and not infected with malignant tumoursby, and the maximum likelihood method was used to estimate the parameters of the logistic model to determine the most important factors affecting. And (Wald) test was used to determine the significance of the explanatory variables, (Person ChiSquare) used for goodness of fit Model, and to know power of model we use (R 2 ) for the logistic model to determine the explanatory variable effect on dependent variable. And to achieve the search of objectives the research partition on the theoretical side was addressed to the analysis of the logistic model, the applied side included data for patients with infected and nontumours infected, obtained from (Rizgarry Hospital) and (Nana Kali Hospital) in Erbil have been reached to conclusions that we believe are important and should be noted by health providers.